(1147) Review and appraisal of economic co-operation and integration efforts in selected countries in the Middle-East مراجعة وتقييم جهود التعاون والتكامل الاقتصادي في بلدان مختارة في الشرق الأوسط - احمد الغندور (معهد التخطيط القومي, 2026)
This paper examines efforts toward economic cooperation and integration among Arab countries, as well as the prospects for deepening such cooperation. Economic cooperation is broadly defined to include a range of regional preferential arrangements, from preferential trade treatment to full economic union. Economic integration is reserved for more advanced forms of cooperation, such as free trade areas and customs unions. The study focuses on seven Arab countries—Egypt, Iraq, Jordan, Kuwait, Lebanon, Saudi Arabia, and Syria—among which several attempts at economic cooperation and integration have been undertaken. The analysis is restricted to cooperation and integration in the field of commodity trade. تتناول هذه الورقة الجهود المبذولة نحو تحقيق التعاون والتكامل الاقتصادي بين الدول العربية، إضافةً إلى آفاق تعميق هذا التعاون في المستقبل. ويُعرَّف التعاون الاقتصادي بشكل عام بأنه يشمل مجموعة من الترتيبات التفضيلية الإقليمية، التي تمتد من المعاملة التجارية التفضيلية إلى الاتحاد الاقتصادي الكامل. أما التكامل الاقتصادي فيُستخدم للإشارة إلى الأشكال الأكثر تقدّمًا من التعاون، مثل مناطق التجارة الحرة والاتحادات الجمركية. تتركز الدراسة على سبع دول عربية هي: مصر، والعراق، والأردن، والكويت، ولبنان، والمملكة العربية السعودية، وسوريا، والتي شهدت فيما بينها عدة محاولات للتعاون والتكامل الاقتصادي. ويقتصر التحليل على مجالات التعاون والتكامل في تجارة السلع.